Would Longer Sentences Lead to More Faithful Translation? Effects of Linguistic Features on Metafunctional Translation Equivalence in Chinese Classics - Yang, Qingxin; Ma, Jianjun; Feng, Lei; Liu, Xin (Theory and practice in language studies, 2025)
Systemic functional linguistics offers translation studies with a metafunctional view, but research on metafunctional translation equivalence remains limited. This study quantifies translation equivalence through a metafunctional framework, focusing on the impact of linguistic features on the translation of Chinese classics. Using the metafunctional equivalent-shift cline as a tool for measurement, this study examines how sentence length, antithesis, and subject ellipsis impact translation equivalence, based on the Bairenbaiyi corpus. The results reveal that translations generally maintain equivalence across the three metafunctions—ideational, interpersonal, and textual—with interpersonal function exhibiting the highest degree of equivalence. Longer sentences correlate with stronger equivalence, while antithesis and subject ellipsis negatively affect equivalence. These findings underscore the critical role of linguistic features of the source text for achieving translation equivalence, supporting Matthiessen's assertion that translation involves decision-making that requires compromises across the metafunctional spectrum.